The Influence of Economic Literacy, Entrepreneurship Education and Entrepreneur Mindset in Improving The Competitiveness of Small and Medium Enterprises" (SMES) with Business Performance as A Moderator Variable - Rijal, Syamsu; Rahmatullah, Rahmatullah; Sriwahyuni, Sriwahyuni; Arisah, Nur; Tadampali, Andi Caezar To (International Journal of Business, Law, and Education, 2025)
This study aims to determine how the influence of Economic Literacy, Entrepreneurial Education and Entrepreneurial Mindset on the Competitiveness of SMEs in Pisang Epe' SMEs actors on Losari Beach, Makassar City through Business Performance as a Moderator variable. Quantitative research is used as a method in this study with a descriptive research type. In this study, the sample used was 100 Pisang Epe' SMEs Actors on Losari Beach, Makassar City. The analysis in this study used Partial Least-Square Structural Equation Modeling (PLS-SEM) with the help of Smart PLS software version 4.0. The study has positive and significant research results between Economic Literacy, Entrepreneurial Education and Entrepreneurial Mindset on Business Performance. The results of the study also between Economic Literacy, Entrepreneurial Education and Entrepreneurial Mindset on SMEs Competitiveness have a positive and significant effect. In this study, Business Performance as a Moderator variable shows that it is able to mediate the relationship between economic literacy and SMEs Competitiveness on Tokopedia positively and significantly. Business performance as a Moderator variable shows that it is able to mediate the relationship between Entrepreneurship Education and SMEs Competitiveness positively and significantly. And the Business Performance variable as a Moderator variable shows that it is able to mediate the relationship between economic literacy and Entrepreneur Mindset positively and significantly.